Biosourced, highly porous, carbon xerogel microspheres. Issue 70 (11th July 2016) - Grishechko, L. I.; Amaral-Labat, G.; Fierro, V.; Szczurek, A.; Kuznetsov, B. N.; Celzard, A.
Abstract : The first tannin-based carbon xerogel microspheres were prepared and characterised. Abstract : The first tannin-based carbon xerogel microspheres were prepared and characterised. The materials were synthesised by inverse emulsion polymerisation in sunflower oil, based on the same formulation but using two main independent variables: stirring speed and surfactant amount. The resultant sol–gel spheres were then washed, dried in air, and pyrolysed. The effect of stirring speed and surfactant amount on carbon microsphere size distribution and porous texture was investigated in detail. Depending on the cases, ultramicroporous carbon microspheres with extremely narrow pore size distributions centred at 0.4–0.5 nm, zero mesoporosity, negligible macroporosity and median diameters close to 40 μm, could be obtained. These characteristics are typical of expensive commercial carbon molecular sieves, whereas the present materials were prepared with cheap and renewable precursors using a very simple method.